Hubungan Penguasaan Kosakata Dengan Kemampuan Menulis Karangan Narasi Siswa Kelas IV UPTD SD Negeri 32 Kabupaten Barru (International Forum of Researchers and Lecturers, 2024)
The main problem in this research is the lack of vocabulary mastery in class IV students at UPTD SD Negeri 32 Barru Regency. This research aims to determine the relationship between vocabulary mastery and the ability to write narrative essays in class IV UPTD students at SD Negeri 32 Barru Regency. This type of research is correlational research and is a quantitative type of research. The sample in this study was 30 students. Data collection techniques were carried out using student learning outcomes tests. The data analysis technique in this research is parametric statistics. After analyzing the data, the researchers found that students' vocabulary mastery and their ability to write narrative essays had a very strong correlation, namely 0.815. rcount = 0.815 and rtable. The results of the analysis show that the value of rcount is greater than rtable (0.815 > 0.361). Based on the results of rcount and rabel, it can be stated that the alternative hypothesis H1 is accepted and Ho is rejected or it can be concluded that based on the achievement of the correlation test significance level Product moment shows that there is a relationship between vocabulary mastery and the ability to write narrative essays in class IV students at UPTD SD Negeri 32 Barru.